ENT530: Facebook sweetgojesshop / Zuraimah Zomadi, Engku Aimi Engku Mohamad Nor Azlan and Nur Syahirah Shahrin - Zomadi, Zuraimah; Engku Mohamad Nor Azlan, Engku Aimi; Shahrin, Nur Syahirah (2017)
Online business today is getting a place in the heart of fashion fans and Muslim clothes. Various applications and methods for online business exist to further develop and support their business. So we welcome this development by doing online business by selling Muslimah shawls and accessories via facebook applications. We are pleased to introduce our online business through facebook which is named 'sweetgojesshop' Besides of selling scarves and accessories such as brooch, we also sell preloves items which are still good and excellent conditions. Our business is run through the facebook application as it is easier for us to reach our customers by using only mobile phones and computers. Customers do not have to go to the store and save time and cost. Through online, it can also help customers choose items more easily and quickly because the item was show, this is because the items we sell in are well organized, attractive, and easy to select. We do not have a specialty store for this business, but customers can buy our goods by accessing sweetgojesshop via facebook and the purchased item will be sent by post or cash on delivery. Customers only need to pay the price of goods and postage only. For our business, most of our items are supply from a good and updated supplier from Kuala Lumpur. This make our shawls and accessories that we sell are very updated and emphasize the simple style but still make u look gorgeous. The material is also from a good quality that can make the users look more attractive. Finally, with the establishment of an online business through this facebook apps, we hope that it can equally help to improve our economic standards and at the same time achieve the target for the subject of PRINCIPLES OF ENTREPRENEURSHIP (ENT530).